Representation of New Media as a Communication Room and Cultural Acculturation of the Baduy Tribe (Ethnographic Study of the Baduy of West Java) - Humaini (IJESS International Journal of Education and Social Science, 2021)
The Baduy tribe is a group of people who have their own values ​​and culture, geographically the Baduy tribe is a group of indigenous peoples in the district of Lebak Banten. There are two areas within the Baduy Tribe, namely the Inner Baduy and Outer Baduy. This tribe is constructed by outsiders with tribes that have their own characteristics and values, ranging from how to dress to procedures or respond to technological tools. This research is purposely to find out how the geographic response of ethnic groups in the province of West Java to respond to information technology (New Media). The research approach using the ethnographic approach is a social science research method that is very intensive in studying the cultural issues of society. The Baduy tribe becomes the object to be studied how the patterns, values, and the daily habits of the tribe in the era of information technology or the New Media era. The results of the study show that the presence of new media provides significance and impact on the daily cultural patterns of the Baduy tribe. New Media brings changes not only to fulfill daily needs such as increasing the economy and getting information. New Media has an impact on the process of studying the habits of the Baduy people or cultural acculturation.